On-Line Learning Using Broadcast Materials: Case study of the BBC on-line learning pilot programme in women's health - Banks, Sheena; McConnell, David (Proceedings of the International Conference on Networked Learning, 2000)
This paper is based on a 1999 evaluation study of the BBC On-line Learning Pilot Programme in Women's Health which was jointly sponsored by the BBC and the Department for Education and Employment. The study involved 4 learning centres based in UK Further Education colleges and 128 learners. The BBC On-line Learning Pilot Programme in Women's Health is an innovative example of how adult learners in different locations can gain access to broadcast media-originated Webbased learning materials with national accreditation. It aimed to attract new learners back into education using the "hook" of broadcast materials via the Internet. The aim of the this qualitative study was to highlight issues about the nature of learner and tutor experiences of BBC On-line learning, discuss the potential of this form of learning for meeting adult learning needs, how to develop good practice in the use of broadcast materials for on-line learning, delivery, costing issues and the opportunities for further development. BBC Education produces a wide range of educational support materials designed to provide adults at home with more information about broadcasts and details about how and where they might take their interest in a subject further, and recently has developed a considerable number of interesting and comprehensive web pages specially designed to support its output and enable the viewer to extend their understanding of what they have seen. This BBC On-line Learning Programme in Women's Health was developed to explore ways in which links could be made between BBC broadcasts, its web sites and digital media to create learning materials. It provided a web-based on-line course which brought together pages from the BBC Education Health site to explore health issues that concern women.